Fishes of the Tomo river, Orinoco basin, Colombia - Javier Alejandro Maldonado-Ocampo; Miryan Lugo; Juan David Bogotá-Gregory; Carlos A. Lasso; Lucena Vásquez; Jose Saulo Usma; Donald C. Taphorn; Francisco Provenzano Rizzi (Biota Colombiana, 2006)
-